Endovascular Treatment of Anterior Communicating Artery Aneurysms: A Systematic Review and Meta-Analysis - Fang, S.; Brinjikji, W.; Murad, M.H.; Kallmes, D.F.; Cloft, H.J.; Lanzino, G. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: Endovascular therapy has become an acceptable alternative to traditional clipping for the management of intracranial aneurysms. However, a limited number of studies have examined outcomes and complications specific to embolization of anterior communicating artery aneurysms. MATERIALS AND METHODS: A systematic review of the literature was conducted with the use of multiple data bases to identify reports on endovascular treatment of anterior communicating artery aneurysms between 1994 and 2012. Angiographic results, clinical outcomes, and complication rates were pooled across studies by using random-effects meta-analysis with subgroup analysis of outcomes by rupture status and time trend stratification. RESULTS: Fourteen studies, consisting of 1552 treated anterior communicating artery aneurysms, were included in this meta-analysis. The rate of immediate and long-term complete and near-complete angiographic occlusion was 88% (95% CI = 81–93%) and 85% (95% CI = 78–90%), respectively. Intraprocedural rupture rate was 4% (95% CI = 3–6%). The re-bleeding rate was 2% (95% CI = 1–4%) and the retreatment rate was 7% (95% CI = 5–12%). Morbidity or mortality caused by perioperative stroke occurred at a 3% (95% CI = 2–6%) rate. Overall procedure-related morbidity and mortality were 6% (95% CI = 4–8%) and 3% (95% CI = 2–4%), respectively. Outcomes did not differ between ruptured and unruptured aneurysms, nor did outcomes change over time, though these latter subanalyses were relatively underpowered. CONCLUSIONS: Endovascular therapy for anterior communicating artery aneurysms is associated with a high rate of complete angiographic occlusion. However, the procedure-related permanent morbidity and mortality are not negligible for aneurysms in this location. AcomAanterior communicating arteryISATInternational Subarachnoid Aneurysm TrialCARATCerebral Aneurysm Rerupture After Treatment